Painting observation changes balance in patients with bilateral vestibulopathy - Adéla Kola; Gaëlle Quarck; Olga Kuldavletova; Thomas Stoffregen; Pierre Denise; Antoine Langeard (PLoS ONE, 2025)
Background Bilateral vestibulopathy (BVP) is a disorder characterized by significant impairments in vestibular function, leading to changes in the kinematics of standing body sway. While previous studies have demonstrated that observing paintings can influence postural control in healthy adults, the effects of such visual stimuli on individuals with BVP remain unexplored. This study aimed to investigate the impact of observing an artistic painting on postural balance. Methods Posture was assessed in 34 patients with bilateral vestibuloapthy compared to 30 healthy controls using three static balance conditions: (1) eyes open by fixating a cross, (2) eyes closed, and (3) while viewing an impressionist painting (Le Bassin aux nymphéas, harmonie verte, Monet, 1899). This painting presents a specific interest due to its perspective cues, providing depth information and spatial reference points, its absence of motion and salient focal point. Results Patients with bilateral vestibulopathy, compared to healthy controls, had higher center of pressure standard deviation and amplitude in the anteroposterior (AP) direction eyes open and eyes closed but no differences between groups were detected when viewing the painting. In addition, the variation of the AP position of the center of pressure was reduced by 20.94% for standard deviation when the BVP patients were looking at the painting in comparison to the standard eyes open condition. Conclusions These findings suggest that art observation can influence postural control in vestibular-defective patients. Further research will be needed to understand the basis of this effect and its possible relevance for rehabilitative treatment.